2023
DOI: 10.1002/dmrr.3651
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the prevention of foot ulcers in persons with diabetes (IWGDF 2023 update)

Abstract: AimsThis is the 2023 International Working Group on the Diabetic Foot guideline on the prevention of foot ulcers in persons with diabetes, which updates the 2019 guideline. This guideline is targeted at clinicians and other healthcare professionals.Materials and MethodsWe followed the Grading of Recommendations, Assessment, Development and Evaluations methodology to devise clinical questions and critically important outcomes in the PICO format, to conduct a systematic review of the medical‐scientific literatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
50
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 54 publications
(63 citation statements)
references
References 100 publications
0
50
0
1
Order By: Relevance
“…1,2 International guidelines underscore the significance of offloading high plantar pressure from DFUs and high peak pressure regions as a key healing and prevention strategy. 3,4 But a good offloading device or shoe can only be effective when worn by the patient and hence adherence is also a central issue.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 International guidelines underscore the significance of offloading high plantar pressure from DFUs and high peak pressure regions as a key healing and prevention strategy. 3,4 But a good offloading device or shoe can only be effective when worn by the patient and hence adherence is also a central issue.…”
Section: Introductionmentioning
confidence: 99%
“…3 After ulcer healing, for the prevention of recurrence, appropriately offloading footwear is recommended in international guidelines. 4 Largely by definition, such footwear is removable, and adherence to treatment is always an aspect of attention in these high-risk patients. Studies have shown that custom-made footwear can be effective in reducing peak pressure at high-risk regions in the foot (where an ulcer just healed), but at the same time that adherence is low and of great concern regarding the prevention of foot ulcers in high-risk people with diabetes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prevalence studies have shown that DFU affects 6.3% of the global diabetes population [8] and has a lifetime incidence in people with diabetes between 19 to 34% [2, 10]. DFU recurrence is also frequent, where 40% of ulcers will reoccur within one year and 65% within three years [2, 10].…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence studies have shown that DFU affects 6.3% of the global diabetes population [8] and has a lifetime incidence in people with diabetes between 19 to 34% [2, 10]. DFU recurrence is also frequent, where 40% of ulcers will reoccur within one year and 65% within three years [2, 10]. In Australia, the prevalence of DFD ranges from 1.2 to 1.5%, while the incidence of diabetes‐related lower limb amputations is between 5.2 to 7.2 per 1000 person‐years.…”
Section: Introductionmentioning
confidence: 99%